Improve the Corrosion Resistance of the Copper-Zinc Alloy by the Epoxy-WO3 Nanocomposite Coating - Ban Abbass; Kadhum Shabeeb; Ayad Hassan (Engineering and Technology Journal, 2021)
Metal corrosion is one of the most critical challenges in industrial processes. In this research, nanocomposite coating was synthesized by blending tungsten trioxide (WO3) nanoparticles with Epoxy resin and applied on brass samples to evaluate the performance of corrosion protection under stressed environments. A dip-coating method was adopted to coat the brass sample's surface. Coated and uncoated brass samples have been subjected to corrosion tests to study the corrosion behavior when exposed to corrosive media. Obtained results indicated that the brass coated samples with mixed epoxy\tungsten trioxide (WO3) exhibited reasonable corrosion resistance because of the ceramic protective barrier on the surface of the metal. Therefore, the proposed methodology could be considered as a promising surface coating that promotes corrosion resistance under stressed industrial conditions.